Hydrogen production from methanol decomposition using Cu-Al spinel catalysts. (10th May 2018) - Li, Guangjun; Gu, Chuantao; Zhu, Wanbin; Wang, Xiaofen; Yuan, Xufeng; Cui, Zongjun; Wang, Hongliang; Gao, Zhixian
Abstract: The development of inexpensive and effective catalysts that can produce hydrogen from methanol is attractive for the implementation of clean energy technologies. Cu-Al oxides, prepared by different methods, were tested for hydrogen production from methanol decomposition. Catalysts with spinel CuAl2 O4 (copper aluminate) structure as compared with non-spinel Cu-Al oxides, are more stable, and exhibit higher catalytic activity despite of their low surface area. Spinel CuAl2 O4 synthesized by citrate process show better performance towards methanol decomposition than that obtained by co-precipitation process. The selectivity to H2 +CO can be improved by the impregnation of potassium in spinel CuAl2 O4 . However, the direct addition of potassium during the citrate process strongly inhibited the formation of CuAl2 O4 structure, thus leading to a low catalytic activity. CuAl2 O4 was found to be a reservoir of Cu, slowly releasing Cu during the catalysis of methanol decomposition and preventing Cu from quick sintering. Graphical abstract: Image Highlights: Various Cu-Al oxides were prepared for H2 production from methanol decomposition. Cu-Al oxides containing spinel structure exhibited stable catalytic activity. The impregnation of potassium in CuAl2 O4 could improve the selectivity of H2 + CO. Direct addition of K during catalyst synthesis strongly inhibited CuAl2 O4 formation. Cu-Al spinel acted a reservoir of Cu, slowly releasing Cu and preventing Cu from quick sintering.